2024
DOI: 10.1101/2024.01.12.24301242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic proteomics in Autosomal dominant Alzheimer’s disease reveals decades-early changes of CSF proteins in neuronal death, and immune pathways

Yuanyuan Shen,
Muhammad Ali,
Jigyasha Timsina
et al.

Abstract: Background To date, there is no high throughput proteomic study in the context of Autosomal Dominant Alzheimers disease (ADAD). Here, we aimed to characterize early CSF proteome changes in ADAD and leverage them as potential biomarkers for disease monitoring and therapeutic strategies. Methods We utilized Somascan 7K assay to quantify protein levels in the CSF from 291 mutation carriers (MCs) and 185 non-carriers (NCs). We employed a multi-layer regression model to identify proteins with different pseudo-traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…We included PC1 of the proteome as a covariate, because previous studies have shown that it represents a large source of non-disease related variance, potentially related to heterogeneity in CSF production/clearance rates 65,67 . Inclusion of PC1 "denoised" the data greatly improved the significance of protein associations with cognitive impairment in every cohort we assessed.…”
Section: Linear Regressionmentioning
confidence: 99%
“…We included PC1 of the proteome as a covariate, because previous studies have shown that it represents a large source of non-disease related variance, potentially related to heterogeneity in CSF production/clearance rates 65,67 . Inclusion of PC1 "denoised" the data greatly improved the significance of protein associations with cognitive impairment in every cohort we assessed.…”
Section: Linear Regressionmentioning
confidence: 99%
“…Leveraging the high-throughput capabilities of the SOMAscan proteomics platform and data from the Dominantly Inherited Alzheimer Network (DIAN), we explored the changes in expression, stability, and modi cations of UPS proteins throughout the disease course. Considering existing evidence that abnormal accumulation of Aβ and tau proteins in the brain in AD begins well before the onset of neurological symptoms, up to 20 years prior, we investigated the early accumulation of both Aβ and tau aggregated protein species in relation to UPS dysregulation in DIAD 28,30,31,32,33 . We aimed to explore if dysregulation of UPS proteins impacts the progression of DIAD by assessing the associations with Aβ, and tau pathologies, neuronal loss, and neuroin ammation (all measured using existing established CSF and neuroimaging biomarkers) and clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%